Meningkatkan keterampilan bermain taktis sepak bola melalui pendekatan model pembelajaran permainan taktis - Tono Nugraha (Indonesian Journal of Educational Development, 2021)
The purpose of this action research is to determine the extent to which the tactical game learning model approach can improve the ability to execute skills, make decisions, support, in soccer game situations. The research subjects were students of Class XII IPS 3, Academic Year 2017/2018 totaling 43 people. The object of research is tactical playing skills. Data on tactical playing skills were collected using observation instruments. Skills assessment is quantitative data from observations which are then converted into qualitative data. The research data were analyzed descriptively qualitatively. This action research is said to be successful if it meets the following criteria: (a) the minimum score for the implementation of the learning process with the criteria "Good", (b) the minimum score for the activities of students in the learning process with the criteria "Good"; (c) the minimum score for the response of students to the learning process with the criteria of "Good"; and (d) minimum score of 'Good' criteria for soccer process skills. The results showed that: (a) in cycle 1 the score was 56.74 with sufficient criteria; (b) in cycle 2 has increased with the acquisition value of 78.86 with good criteria. In conclusion, the tactical game learning model approach can improve tactical playing skills in soccer game situations. Tujuan penelitian tindakan ini adalah untuk mengetahui sejauh mana pendekatan model pembelajaran permainan taktis dapat meningkatkan kemampuan keterampilan mengeksekusi, membuat keputusan, mendukung, dalam situasi permainan sepak bola. Subjek penelitian adalah peserta didik Kelas XII IPS 3, Tahun Pelajaran 2017/2018 berjumlah 43 orang. Objek penelitian adalah keterampilan bermain taktis. Data keterampilan bermain taktis dikumpulkan menggunakan instrumen observasi. Penilaian keterampilan merupakan data kuantitatif hasil observasi kemudian dikonversi menjadi data kualitatif. Data hasil penelitian dianalisis secara deskriptif kualitatif. Penelitian tindakan ini dikatakan berhasil apabila memenuhi kriteria: (a) skor minimal pelaksanaan proses pembelajaran kriteria “Baik”, (b) skor minimal aktivitas pesrta didik pada proses pembelajaran kriteria “Baik”; (c) skor minimal respon peserta didik pada proses pembelajaran kriteria “Baik”; dan (d) skor minimal keterampilan proses permainan sepak bola kriteria ‘Baik”. Hasil penelitian menunjukkan bahwa: (a) pada siklus 1 perolehan nilai 56,74 dengan kriteria cukup; (b) pada siklus 2 mengalami peningkatan dengan perolehan nilai 78,86 dengan kriteria baik. Kesimpulan, pendekatan model pembelajaran permainan taktis dapat meningkatkan keterampilan bermain taktis dalam situasi permainan sepak bola.